Variasi Bahasa Dalam Film Animasi Nussa & Rara Di Youtube - Ulfa Kurnia; Pahrul. R (Sociale : Journal of Social Science, 2026)
This study aims to determine This study aims to determine the description of literacy in the form of language alteration in the Nussa & Rara animated film episode